An exercise in resistance: Inoculation messaging as a strategy for protecting motivation during a monotonous and controlling exercise class - Dimmock, J.; Gagné, Marylène; Proud, L.; Howle, T.; Rebar, A.; Jackson, B. (Human Kinetics, 2016)
Sustained attention has been devoted to studying the factors that support (or thwart) individuals' enjoyment of, interest in, and value judgments regarding their exercise activities. We employed a resistance-inducing (i.e., inoculation theory) messaging technique with the aim of protecting these desirable perceptions in the face of environmental conditions designed to undermine one's positive exercise experiences. Autonomously motivated exercisers (N = 146, Mage= 20.57, SD = 4.02) performed a 25-min, group-based, instructor-led exercise circuit, in which the activities were deliberately monotonous, and during which the confederate instructor acted in a disinterested, unsupportive, and critical manner. Shortly before the session, participants received either a control message containing general information about the exercise class or an inoculation message containing a forewarning about potential challenges to participants' enjoyment/interest/value perceptions during the class, as well as information about how participants might maintain positive perceptions in the face of these challenges. Despite there being no between-conditions differences in presession mood or general exercise motives, inoculated (relative to control) participants reported greater interest/enjoyment in the exercise session and higher perceptions of need support from the instructor. Perceptions of need support mediated the relationship between message condition and interest/enjoyment.